Surgical management of lymphoma of third eyelid in a German Shepherd dog - Das, Babita; Singh, Randhir; Ramyavani, Kotari Beulah; Dubey, Amita; Shahi, Apra; Jawre, Shobha; Mishra, Apoorva (Indian Journal of Veterinary Surgery, 2026)
-